Winning with data : transform your culture, empower your people, and shape the future - Tunguz, Tomasz , 1981-; Bien, Frank , 1967- (Wiley, 2016)
"Crest the data wave with a deep cultural shift Creating a Data-Driven Culture explores the cultural changes big data brings to business, and shows you how to adapt your organization to leverage data to maximum effect. Authors Tomasz Tunguz and Frank B